MY FAVOURITE MUSLIM HERO: A LEARNING DESIGN DEVELOPMENT OF ONLINE PROJECT-BASED LEARNING (PJBL) USING ASSURE MODEL - Rifan Nurrofi; Ulfa, Saida; Soepriyanto, Yerry; Farah, Rafika Rabba (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
Project-based learning is one of the inquiry models that is often carried out in higher education; however, the application of online-based PjBL in English paragraph writing with Muslim friendly topic is still limited. This research aims to develop an online-based PjBL learning design that focuses on creating infographic of inspiring Muslim figures in a project-based design. The development of learning design implemented the ASSURE model, with six stages. The online-based media used include Google Classroom, Google Docs, Padlet, Zoom, Wakelet, Miro for interactive discussions, and Canva for infographic design. Trials were carried out and expert in the field validated the learning design. After validation satge, the learning design was implemented with students for testing. The developed learning syntax was validated as effective. Then, the online-based learning media and lesson timeline are also declared valid. Thus, these two trials were deemed suitable for implememntation with students. Furthermore, the learning strategy design and results were validated and interesting based on positive responses from experts and students. It is concluded that the development results meet the research objectives. The results of this research implies that online PjBL in English writing class can be effectively implemented to Muslim students at islamic institution context.